PATTERNS AND CHARACTERISTICS OF OLD CITY MORPHOLOGY (CASE STUDY FORT MARLBOROUGH, KAMPUNG CHINA AND KAMPUNG MALABERO KOTA BENGKULU) - Fitrianty Wardhani (Journal of Architecture&ENVIRONMENT, 2019)
Urban Morphologyis an applied science that studies about how the pattern of a city spacewere made by the history,andalsolearn about the development of a city. The old city area of Bengkulu is a British-formed city starting in 1719 which has special characteristics. This paper aims to identify the pattern and special characteristics of the old city morphology inFort Marlborough Region,China Town,andTapak Paderi area inBengkulu City. Methodology used in this study is a qualitative descriptivewith diachronic reading and typo-morphplogy  analysis. To get the pattern and characteristicsof those mentioned areas, detail aspects such as buildings and materials, road and block patterns, land use activities and open spaceswere used as an indicator. Result of the studies shows that there is a changein theurban planning of Bengkulu city. At first, British colonial planned Bengkulu as a port and trade city where the beach of the bay area was the center of the city. But later, with the development of the city, Bengkulu is no longer a seaside cityanymore. Now, Bengkulu has been growth towards the south and westof the city. It’s showed by the transfer of the city center fromfortress area intothe Bentiring area. In term of material, road and block patterns,and also land use activities,can be seen that there was a concentrationofroad and block patternswhere almost allthe blocks had the same size withclose distance, at first of British colonialism.There are also three main nodes which confirm the city center,along with another small nodesthat markthe city area. But now days, morphologicalcharacteristicsof Bengkulu cityespecially for the road and block patterns are heterogeneous,where there are two or more patterns werecollides, and the main road axis have north-south pattern.The buildings also have changed, fromadoption of European architecturesat first, into vernaculararchitecture that adapts Indonesian climateby using gable and shieldroof now.